Governar pela autonomia: universidade, inovação e capitalismo cognitivo - Murilo Duarte Costa Corrêa; João Guilherme Pereira Chaves; Diego Petyk de Sousa (EccoS – Revista Científica)
The second academic revolution occurred during the XX and XXI centuries, was characterized by the integration of the universities within developement and social goals, and constitutes the source of university and economy interdependence. This essay describes how the recent transformations of university autonomy embodied neoliberal patterns of government. Therefore, the paper reviews the literature on the entrepreneur university and discusses the related settings on economics and politics through Michel Foucault’s post-structuralism and cognitive capitalist theorists, such as Maurizio Lazzarato and Franco Berardi. The research suggests that the transformations of the university autonomy and the new global and immaterial capitalist dynamics go along. In this context the university autonomy is converted into a form of government adjusted to cognitive capitalism and finance ion, becoming the key element of an emerging Neo-liberal paradigm of government.